ChemInform Abstract: Structure, Ionization, and Fragmentation of Hydrogenated Aluminoboron Clusters: Al2B2H2n (n = 0—6). Issue 45 (October 2016) - Muz, Iskender; Canko, Osman; Atis, Murat
Abstract: Energetic and structural stability of Al2 B2 H2n (n = 0—6) clusters is investigated by DFT calculations and a stochastic search algorithm.